Operation efficiency analysis of the Small Animal Clinic, University Veterinary Hospital - Lim, Zhi Jian (2015)
Turnaround time (TAT) is an important determinant for workflow efficiencies in various healthcare facilities, including veterinary facilities. The objectives of this study were to determine the TAT of different service stations during consultation and treatment at the Small Animal Clinic (SAC), University Veterinary Hospital (UVH), and to identify possible factors that affect the TAT at each service station. A clinical workflow structure was established and each service station was defined. The service stations are reception, examination/biopsy/treatment, minilab, X-ray/ultrasound, interpretation and diagnosis, verification/dispensary, payment, and dispensary. TAT data was recorded for each service station during consultation using both computerized and manual recording methods. Details of the cases and other relevant information were recorded. The dataset was then analyzed using SPSS version 20. The mean TATs for each service station ranged from 1.96 mins (dispensary) to 42.10 mins (reception). Factors that determined TATs included the attributes of cases and human resource factors. The average revenue per cases for the duration of the study was RM 166.10 per case, with the highest recorded on Mondays (RM 194.23) and lowest on Saturdays (RM 77.99). In conclusion, this study showed that the TAT is closely related to the nature of cases and inputs in human resource. Therefore the current findings could be use as a reference to further improve the service efficiencies of the SAC, UVH.